Skeletal Muscle - Campbell, Kevin P.; Glass, David J.; Rudnicki, Michael A.
The only open access journal in its field, Skeletal Muscle publishes novel, cutting-edge research and technological advancements that investigate the molecular mechanisms underlying the biology of skeletal muscle. Reflecting the breadth of research in this area, the journal welcomes manuscripts about the development, metabolism, the regulation of mass and function, aging, degeneration, dystrophy and regeneration of skeletal muscle, with an emphasis on understanding adult skeletal muscle, its maintenance, and its interactions with non-muscle cell types and regulatory modulators. Main areas of interest include: differentiation of skeletal muscle atrophy and hypertrophy of skeletal muscle aging of skeletal muscle regeneration and degeneration of skeletal muscle biology of satellite and satellite-like cells dystrophic degeneration of skeletal muscle energy and glucose homeostasis in skeletal muscle non-dystrophic genetic diseases of skeletal muscle, such as Spinal Muscular Atrophy and myopathies maintenance of neuromuscular junctions roles of ryanodine receptors and calcium signaling in skeletal muscle roles of nuclear receptors in skeletal muscle roles of GPCRs and GPCR signaling in skeletal muscle other relevant aspects of skeletal muscle biology In addition, articles on translational clinical studies that address molecular and cellular mechanisms of skeletal muscle will be published. Case reports are also encouraged for submission. Skeletal Muscle reflects the breadth of research on skeletal muscle and bridges gaps between diverse areas of science for example cardiac cell biology and neurobiology, which share common features with respect to cell differentiation, excitatory membranes, cell-cell communication, and maintenance. Suitable articles are model and mechanism-driven, and apply statistical principles where appropriate; purely descriptive studies are of lesser interest.